Scalable VR Solutions for Engineering Education: A Continuous Improvement Framework - Steed, Clint Alex; Mangaroo-Pillay, Mia; Wolff, Karin (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
The increasing use of technology in higher education, especially in resource-constrained environments, is reshaping how students engage with industrial experiences. Virtual Reality (VR) offers a solution to the challenges posed by growing class sizes and limited real-world access, supporting holistic Graduate Attribute Development and addressing global SDG challenges in engineering education. This paper explores how VR can enhance student engagement with complex technological topics like Industry 4.0. It examines the effectiveness of a VR-based framework for improving student emotional responses and interest in technology, while assessing the scalability of such approaches for larger classes. A pilot study was conducted with third- and fourth-year students participating in a voluntary virtual facility layout activity. Emotional response surveys showed that fourth-year students were more comfortable with the technology, as expected, but both groups reported increased interest in technological topics. The study uses a dynamic response evaluation model informed by these surveys, and the organizational distinction between development teams and lecturing staff enables the framework to scale effectively. The findings demonstrate that VR can improve student engagement and comfort with emerging technologies, making it an important tool for resource-constrained environments. This framework provides a method for continuous improvement, quantifying the long-term impact of VR on engineering education curricula. By enabling adaptable, scalable learning experiences, it helps prepare students for complex engineering challenges and future technological changes, offering a valuable contribution to the ongoing evolution of engineering education.